Portrait of Sexual Abuse in Vanessa Wye in Novel My Dark Vanessa - Farah Rasfia Putri (Syntax Idea)
The study aims to identify the forms of sexual harassment experienced by the main female character, Vanessa Wye, then the data will be searched using reading and recording techniques. After successfully obtained, the collected data will be discussed using descriptive-qualitative methods. So that in the end, this research will produce forms of violence or sexual harassment experienced by Vanessa Wye. Cases of sexual violence and abuse of children and women are very alarming crimes. Every year many victims experience sexual abuse. This phenomenon is also illustrated in the novel My Dark Vanessa by Kate Elizabeth Russell. The novel tells the story of a sexual relationship between a 15-year-old student named Vanessa Wye and Jacob Strane who is already her 42-year-old English teacher, presented from the perspective of an adult Vanessa Wye who is 30 years old. The researcher chose the novel because it was the research theme to be discussed. In this study, researchers used Kelly's theory which explains the forms of sexual harassment which are divided into 3 parts, namely Visual, Verbal, and Physical. Using the theory and mimetic approach.